2018
DOI: 10.1161/strokeaha.118.020163
|View full text |Cite
|
Sign up to set email alerts
|

Arterial Stiffness Is Associated With Basal Ganglia Enlarged Perivascular Spaces and Cerebral Small Vessel Disease Load

Abstract: We found that, in a cohort of hypertensive individuals, the arterial stiffness is associated with the total load of the cSVD, especially with lacunes and basal ganglia EPVS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 9 publications
4
57
2
2
Order By: Relevance
“…IMT and plaque were thought to reflect the pathological changes of carotid atherosclerosis, while baPWV and ABI suggested large artery stiffness. In this study, our findings revealed that baPWV was positively associated with four CSVD markers and total disease burden, which was in accordance with previous studies 24 , 39 ) , while others had significant associations with some CSVD markers. Therefore, we considered that baPWV may be clinically more useful in discriminating the presence of small vessel diseases.…”
Section: Discussionsupporting
confidence: 93%
“…IMT and plaque were thought to reflect the pathological changes of carotid atherosclerosis, while baPWV and ABI suggested large artery stiffness. In this study, our findings revealed that baPWV was positively associated with four CSVD markers and total disease burden, which was in accordance with previous studies 24 , 39 ) , while others had significant associations with some CSVD markers. Therefore, we considered that baPWV may be clinically more useful in discriminating the presence of small vessel diseases.…”
Section: Discussionsupporting
confidence: 93%
“…The cause of dilated perivascular spaces is still under debate. They have been associated with other vascular risk factors for CSVD, such as elevated blood pressure (Klarenbeek et al, 2013; Yakushiji et al, 2014; Yao et al, 2014; Gutierrez et al, 2015) and large-vessel abnormalities (Gutierrez et al, 2013; Riba-Llena et al, 2018), however these results are not consistent in the literature (Bouvy et al, 2016). Thus although perivascular spaces seem to share similar risk factors as other measures of CSVD, more research is warranted.…”
Section: Perivascular Spacesmentioning
confidence: 90%
“…Finally, the association between BGPVS and ICH might be mediated by a shared underlying mechanism. For example, arterial stiffening has recently been associated with BGPVS 22 , adjusted for major vascular risk factors, and also with deep ICH cross-sectionally and new CMB formation prospectively 23,24 . By reducing damping of the cardiac impulse and increasing transmission of pulsatile force to small cerebral arteries 25 ,…”
Section: Discussionmentioning
confidence: 99%